Regional Financial Performance, Audit Function, and Corruption Levels in Indonesia - Suhardjanto, Djoko; Djuminah, Djuminah; Agustiningsih, Sri Wahyu (Jurnal Akuntansi dan Bisnis, 2020)
This study aims to examine the effect of financial performance on the level of corruption of the provincial government in Indonesia is moderated by audit findings. This research is motivated by Indonesia's efforts to fight corruption as an extraordinary crime. The development of corrupt practices has also increased since the implementation of the decentralization program. The phenomenon of increasing the level of regional corruption since the implementation of regional autonomy is the reason that observing the level of regional corruption is still necessary. This research was conducted in all 34 provincial governments in Indonesia, with an observation period of 2011-2015. The sample of this study was 156 sample data, obtained from financial data of 34 provinces for 5 years, and outlier data were 14 sample data. Analysis of the data in this study uses moderated regression analysis (MRA). The research concept was developed to predict the level of audit findings in moderating the effect of financial performance on the level of corruption in Indonesia. Test results in this study indicate that the audit findings moderate the effect of the ratio of operating expenses and the ratio of capital expenditure to the level of corruption. While other results indicate that the audit findings do not moderate the effect of the level of independence of a region on the level of corruption.Penelitian ini bertujuan untuk menguji pengaruh kinerja keuangan terhadap tingkat korupsi pemerintah daerah provinsi di Indonesia dimoderasi dengan temuan audit. Penelitian ini dilatarbelakangi oleh upaya Indonesia untuk memerangi korupsi sebagai kejahatan luar biasa. Perkembangan praktik korupsi semakin meningkat juga sejak diterapkannya program desentralisasi. Fenomena peningkatan tingkat korupsi daerah sejak diimplementasikannya otonomi daerah ini menjadi alasan bahwa pengamatan terhadap tingkat korupsi daerah masih merupakan hal perlu untuk dilakukan. Penelitian ini dilakukan di seluruh 34 pemerintah daerah provinsi di Indonesia, dengan periode pengamatan tahun 2011-2015. Sampel penelitian ini sebesar 156 data sampel, yang diperoleh dari data keuangan 34 propinsi selama 5 tahun, dan data outlier sebanyak 14 data sampel. Analisis data penelitian ini menggunakan moderated regression analysis (MRA). Konsep penelitian dikembangkan untuk memrediksi tingkat temuan audit dalam memoderasi pengaruh kinerja keuangan terhadap tingkat korupsi di Indonesia. Hasil pengujian dalam penelitian ini menunjukan bahwa temuan audit memoderasi pengaruh rasio pengeluaran operasional dan rasio belanja modal terhadap tingkat korupsi. Sementara hasil lainnya menunjukkan bahwa temuan audit tidak memoderasi pengaruh tingkat independensi suatu daerah terhadap tingkat korupsi.